Gaussian periods in cyclotomic fields and relative traces as generators of intermediate subfields. - Gómez-Molleda, María de los Ángeles (Springer Nature, 2018)
We study relative traces to provide primitive elements for all the subfields of any cyclotomic field. We also build a primitive element for a cyclotomic extension such that every intermediate field is generated by its relative trace.
https://openpolicyfinder.jisc.ac.uk/id/publication/36174
Keywords: Números, Teoría algebraica de; Cuerpos de clase, Teoría de; Cyclotomics; Trace; Subfields